2019
DOI: 10.1002/btpr.2880
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the interplay between scaffold geometry, induced shear stresses, and cell proliferation within a packed bed perfusion bioreactor

Abstract: By favoring cell proliferation and differentiation, perfusion bioreactors proved efficient at optimizing cell culture. The aim of this study was to quantify cell proliferation within a perfusion bioreactor and correlate it to the wall shear stress (WSS) distribution by combining 3‐D imaging and computational fluid dynamics simulations.NIH‐3T3 fibroblasts were cultured onto a scaffold model made of impermeable polyacetal spheres or Polydimethylsiloxane cubes. After 1, 2, and 3 weeks of culture, constructs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 63 publications
(138 reference statements)
2
11
0
Order By: Relevance
“…[ 48 ] In another study, it has been reported that shearing flow did not have a significant effect on MSCs proliferation, using a parallel plate flow chamber. [ 49 ] In contrary, other studies reported enhanced proliferation of MSCs and NIH‐3T3 fibroblasts [ 50,51 ] in dynamic cultures using scaffolds. Such contradictory findings may be due to the use of different shear stress magnitudes and modes.…”
Section: Resultsmentioning
confidence: 94%
“…[ 48 ] In another study, it has been reported that shearing flow did not have a significant effect on MSCs proliferation, using a parallel plate flow chamber. [ 49 ] In contrary, other studies reported enhanced proliferation of MSCs and NIH‐3T3 fibroblasts [ 50,51 ] in dynamic cultures using scaffolds. Such contradictory findings may be due to the use of different shear stress magnitudes and modes.…”
Section: Resultsmentioning
confidence: 94%
“…The samples were scanned by X-ray micro-tomography and the tridimensional arrangements of the beads and the tissue were obtained after image reconstruction. Preliminary experiments showed that tissue proliferation on glass and polyacetal bead stacks in static conditions (without flow) was negligible compared to dynamic conditions [39,40], producing too little tissue volume to be resolved by X-ray microtomography. Additionally, mass transport estimates in similar culture conditions and close flow rate indicate that oxygen and nutrient supply is in excess during most of the three weeks of culture [39].…”
Section: Resultsmentioning
confidence: 99%
“…The cylindrical growth chamber (13.8 mm diameter, 5 cm high, made of polycarbonate) is randomly filled by mono disperse polyacetal beads (2 mm diameter). Let us note that bead-based scaffolds have been identified as good candidates for tissue engineering and therefore have been investigated multiple times [4,32,39,40,[44][45][46][47]. The beads are immobilized by two polycarbonate grids (0.5 cm high), inserted in the growth chamber at the bioreactor inlet and outlet.…”
Section: Perfusion Bioreactormentioning
confidence: 99%
See 2 more Smart Citations